Coordination of international multicenter studies: governance and administrative structure - Bangdiwala Shrikant I.; Paula Cristiane S. de; Ramiro Laurie S.; Muñoz Sergio R. (Instituto Nacional de Salud Pública, 2003)
A well-conducted multicenter study needs to assure standardization, uniformity of procedures, high data quality, and collaboration across sites. This manuscript describes the organization and dynamics of multicenter studies, focusing on governance and administrative structures among countries of diverse cultures. The organizational structure of a multicenter study is described, and a system for oversight and coordination, along with roles and responsibilities of participants in the multicenter study, are presented. The elements of a governance document are also reviewed, along with guidelines and policies for effective collaboration. The experience of an ongoing multi-country collaboration, the World Studies of Abuse in the Family Environment (WorldSAFE), illustrates the implementation of these guidelines. It is essential that multicenter studies have an objective coordinating center and that the investigators jointly develop a written governance document to enable collaboration and preserve collegiality among participating investigators.